2012
DOI: 10.1152/ajpheart.00908.2011
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(1–7) attenuates angiotensin II-induced cardiac remodeling associated with upregulation of dual-specificity phosphatase 1

Abstract: Chronic hypertension induces cardiac remodeling, including left ventricular hypertrophy and fibrosis, through a combination of both hemodynamic and humoral factors. In previous studies, we showed that the heptapeptide ANG-(1-7) prevented mitogen-stimulated growth of cardiac myocytes in vitro, through a reduction in the activity of the MAPKs ERK1 and ERK2. In this study, saline- or ANG II-infused rats were treated with ANG-(1-7) to determine whether the heptapeptide reduces myocyte hypertrophy in vivo and to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
65
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 43 publications
10
65
0
2
Order By: Relevance
“…A similar action was described for AVE0991 (Sheng-Long et al, 2012). This feature appears not to be restricted to VSMC, considering that Ang-(1-7) has well documented antiproliferative effects in other cell types, including cardiac fibroblasts (McCollum et al, 2012) and tumoral cells (Gallagher and Tallant, 2004;Ni et al, 2012). The involvement of Mas in these Ang-(1-7) effects was supported by the use of the Mas antagonist A-779.…”
Section: Mas-related G Protein-coupled Receptors and Mas In Cardiosupporting
confidence: 55%
See 2 more Smart Citations
“…A similar action was described for AVE0991 (Sheng-Long et al, 2012). This feature appears not to be restricted to VSMC, considering that Ang-(1-7) has well documented antiproliferative effects in other cell types, including cardiac fibroblasts (McCollum et al, 2012) and tumoral cells (Gallagher and Tallant, 2004;Ni et al, 2012). The involvement of Mas in these Ang-(1-7) effects was supported by the use of the Mas antagonist A-779.…”
Section: Mas-related G Protein-coupled Receptors and Mas In Cardiosupporting
confidence: 55%
“…Accordingly, He et al (2004), and later on many other investigators (Iwata et al, 2005;Tallant et al, 2005;Grobe et al, 2006;Iusuf et al, 2008;Mercure et al, 2008;Li et al, 2009;Giani et al, 2010;Gomes et al, 2010;Pei et al, 2010;Varagic et al, 2010;Iwata et al, 2011;Durik et al, 2012;McCollum et al, 2012;Patel et al, 2012;Zeng et al, 2012;de Almeida et al, 2013), described antiremodeling effects of Ang-(1-7) and of other Mas agonists (AVE 0991/CGEN-856S) (Ferreira et al, 2007;Savergnini et al, 2010). These observations are in line with the deleterious cardiac effects of genetic ablation of Mas in mice (Santos et al, 2006;Gava et al, 2012).…”
Section: Mas-related G Protein-coupled Receptors and Mas In Cardiomentioning
confidence: 75%
See 1 more Smart Citation
“…Consistent with this, further in vivo studies using genetically engineered mice also found that ACE3 provides protective effects against chronic pressure overload‐induced cardiac hypertrophy, fibrosis, and dysfunction. Accumulating evidence has pointed out that ACE2 and its primary product Ang 1 to 7 play critical roles in the pathophysiology of cardiovascular disease, especially the protective actions against pathological cardiac hypertrophy 20, 21. We demonstrated that ACE3, as a new component of the ACE family, has the ability to impair Ang II‐ and pressure overload‐induced cardiac hypertrophy in this study.…”
Section: Discussionsupporting
confidence: 58%
“…After the identification of MasR as the main receptor for Ang-(1-7) [92], the protective role of Ang-(1-7)/MasR axis has been shown in endothelial dysfunction [119], global ischemia [120], ischemia/reperfusion (I/R) [116], MI [121], cardiac remodeling [122] and HF [123]. It is widely known that I/R induces arrhythmias and contractile dysfunction in cardiac cells and that Ang-(1-7) has a cardioprotective role.…”
Section: Angiotensin-(1-7) and Cardiovascular Diseasesmentioning
confidence: 99%